The Failure of Subsidy Policies In Conditions of Information Asymmetry : Theoretical and Empirical Analysis - Ferizaldi Ferizaldi (PT. Anagata Sembagi Education, 2026)
Subsidy policy is an instrument of state intervention aimed at improving welfare distribution and correcting market failures. However, its effectiveness often does not align with its formulated normative objectives. This study aims to analyze the failure of subsidy policy by positioning information asymmetry as a key structural determinant influencing policy design, implementation, and outcomes. The research approach uses a theoretical-analytical qualitative method, combining studies of public economic theory, information asymmetry theory, and institutional perspectives, as well as a critical analysis of empirical findings from various policy documents and previous studies. The analysis shows that information asymmetry between the government, subsidy recipients, and intermediary actors results in inaccurate targeting, incentive distortion, and systemic opportunistic behavior. The gap between the normative design of the policy and the reality of empirical implementation is exacerbated by limited administrative capacity, institutional fragmentation, and weak public information systems. These conditions not only reduce the effectiveness of subsidy policy but also create a significant fiscal burden and hamper the sustainability of public policy. This study emphasizes the importance of reformulating subsidy policy through strengthening governance, integrating information systems, and shifting the paradigm towards recipient-based subsidies. The integration of theoretical and empirical analysis provides a more realistic conceptual basis for the formulation of adaptive, accountable, and sustainable subsidy policies.